novel activator-type ERF of Thinopyrum intermedium, TiERF1, positively regulates defence responses - Liang, HongXia; Lu, Yan; Liu, HongXia; Wang, FengDe; Xin, ZhiYong; Zhang, ZengYan (Journal of experimental botany, 2008)
Thinopyrum intermedium is resistant to many different pathogens. To understand the roles of ethylene response factors (ERFs) in defence responses, the first member of the ERF family in T. intermedium, TiERF1, was characterized and functionally analysed in this study. The TiERF1 gene encodes a putative protein of 292 amino acids, belonging to the B3 subgroup of the ERF transcription factor family. Biochemical assays demonstrated that the TiERF1 protein is capable of binding to the GCC box, a cis-element present in the promoters of pathogenesis-related (PR) genes, and possessing transactivation activity, as well as localizing to the nucleus. The transcript of TiERF1 in T. intermedium is rapidly induced by infection with Rhizoctonia cerealis, Fusarium graminearum, or Blumeria graminis, and ethylene, jasmonic acid, and salicylic acid treatments. More importantly, the ectopic expression of TiERF1 in tobacco activated the transcript of the PR genes of tobacco with a GCC box cis-element, and ACO and ACS genes key to ethylene synthesis, and in turn improved the resistance level to Alternaria alternata and tobacco mosaic virus, as well as causing some phenotypic changes associated with ethylene response in the transgenic tobacco plants. Taken together, TiERF1 protein as an ERF transcription activator positively regulates defence responses via the activation of some defence-related genes.